2015
DOI: 10.5812/ijvlms.12010
|View full text |Cite
|
Sign up to set email alerts
|

Modified Unified Theory of Acceptance and Use of Technology in Investigating Iranian Language Learners’ Attitudes Toward Mobile Assisted Language Learning (MALL)

Abstract: Introduction: The modified unified theory of acceptance and use of technology (MUTAUT) was used in this mixed methods study to investigate language learners' attitudes toward mobile assisted language learning (MALL). Methods: Two different student surveys were used to collect data quantitatively. The surveys consisted of 24 and 23 items, respectively, rated on a 6-point Likert scale. Reliability was estimated to be 0.92 and 0.95, respectively. To collect data qualitatively, language learners were interviewed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Unlike prior studies which revealed non-correlation or positive correlation between SI and BI [27,58], this study proved that SI was negatively related to BI. After reviewing answers to the open-ended question in the survey, we assume that peer pressure might be a possible reason for deterring people from intending to use gamified vocabulary apps.…”
Section: Social Influence (Si) and Behavioral Intention (Bi)contrasting
confidence: 99%
See 2 more Smart Citations
“…Unlike prior studies which revealed non-correlation or positive correlation between SI and BI [27,58], this study proved that SI was negatively related to BI. After reviewing answers to the open-ended question in the survey, we assume that peer pressure might be a possible reason for deterring people from intending to use gamified vocabulary apps.…”
Section: Social Influence (Si) and Behavioral Intention (Bi)contrasting
confidence: 99%
“…Effort expectancy in UTAUT referred to the expected degree of ease using a particular system, which was derived from Technology Acceptance Model (TAM) [25]. In many studies of mobile-assisted language learning (MALL), EE correlated with BI [23,26,27]. However, some studies found contradictory results with EE neither influencing BI nor being a significant predictor of BI [28,29].…”
Section: Effort Expectancymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, many more sophisticated types of technology have been developed recently. Over the past three decades, technology has made significant inroads into educational settings (1)(2)(3). Technology may affect the ways of thinking, decision making, teaching, and learning processes, curriculum development, materials production, as well as evaluation of teaching and learning (4).…”
Section: Introductionmentioning
confidence: 99%